Understanding corruption how corruption works in practice. (AGENDA PUBLISHING, 2022)
Using case studies to understand the different forms of corruption (bribery, political corruption, kleptocracy and corrupt capital) the book builds a picture of the global threat that corruption poses and the responses that have been most effective.